2002
DOI: 10.1021/la0115785
|View full text |Cite
|
Sign up to set email alerts
|

In-Plane Patterning of Aggregated Nanoparticle Layers

Abstract: An in-plane patterning process of aggregated nanoparticle thin layers of different inorganic conducting and semiconducting materials produced in Langmuir−Blodgett precursors is developed using film irradiation with an electron beam. This film treatment performs cross-linking of the precursor organic molecules resulting in the insolubility of the hydrocarbon matrix in organic solvents and in the impossibility of particle aggregation in the exposed regions. After immersion of the film into the organic solvent, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
(50 reference statements)
1
12
0
Order By: Relevance
“…An interesting application of such nanoparticle-LB film composites has been recently shown by Erokhin and co-workers [118]. They have shown that in-plane patterning of nanoparticle films may be accomplished by a simple electron irradiation process as illustrated in Fig.…”
Section: Nanoparticle Formation By Reaction Of Metal Ions Inmentioning
confidence: 96%
See 3 more Smart Citations
“…An interesting application of such nanoparticle-LB film composites has been recently shown by Erokhin and co-workers [118]. They have shown that in-plane patterning of nanoparticle films may be accomplished by a simple electron irradiation process as illustrated in Fig.…”
Section: Nanoparticle Formation By Reaction Of Metal Ions Inmentioning
confidence: 96%
“…Subsequently, a number of groups have investigated this approach from different angles and have reported on the in situ synthesis of nanoparticles of gold [106], CdI 2 [107], CdS [101, 108± 113], CdSe [114], PbS [115±118], TiO 2 [119], copper and copper sulfide [118,120,121] to name just some of the chemical compositions investigated. While not always leading to the formation of nanoparticles, the chemical insertion method in LB films has also been used with considerable success in realizing ultrathin films of oxides such as TiO 2 [122], Y 2 O 3 [123], ZnO [124,125] and Er 2 O 3 [126].…”
Section: Nanoparticle Formation By Reaction Of Metal Ions Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the functionality is naturally patterned. [5][6][7] For example, Won et al bound dendrimers on a surface, then let gold ions adsorb to the dendrimers. By UV irradiation with a photomask, patterned Au nanoparticle structures were obtained.…”
Section: Introductionmentioning
confidence: 99%